MINERALOGY, PETROLOGY, CHEMISTRY, AND 39AR-40AR AND EXPOSURE AGES OF THE CADDO COUNTY IAB IRON: EVIDENCE FOR EARLY PARTIAL MELT SEGREGATION OF A GABBRO AREA RICH IN PLAGIOCLASE-DIOPSIDE - Takeda H.; Bogard D.D.; Mittlefehldt D.W.; Garrison D.H. (My University, 2000)
We describe coarse-grained gabbroic material rich in plagioclase and diopside in the Caddo County IAB iron meteorite. The gabbro is not a clast within a breccia, but rather is an area with transitional margins located mainly at silicate-metal boundaries only a few cm away from fine-grained, ultramafic silicates similar to winonaites. Medium-grained orthopyroxene and olivine are found in transitional areas and show no shock disturbance of their textures. A vein-like region, starting in an area of fine-grained ultramafic silicate, extends towards the gabbroic area with a gradual increase in abundance of plagioclase and diopside. These textures and mineralogies suggest that the gabbroic materials were formed by inhomogeneous segregation of partial melts from chondritic source materials. Compositional data on two mineralogically distinct samples of the gabbro-rich portion of the inclusion were obtained by INAA. Compared to an average of IAB silicate inclusions or winonaites, the Caddo County gabbro is enriched in the incompatible lithophile elements Na, Ca, Sc, REE and Hf, consistent with a melt origin for the gabbro. The cosmogenic space exposure age of Caddo County (5 +/- 1 Ma) is significantly younger than exposure ages of some other IAB meteorites. An 39Ar-40Ar age determination of the gabbroic material indicates a series of upward steps in age from 4.516 Ga to 4.523 Ga, with a few high temperature ages up to 4.54 Ga. The older age could approximate the primary recrystallization age of silicates. The stepped Ar age spectrum may indicate differences in Ar closure temperatures during slow cooling of ~2-20°C/Myr in the parent body. Alternatively, the younger Ar-Ar ages may date a shock event which occurred while Caddo County was hot and which also created textures such as a linear metal vein with rounded zigzag walls in a diopside crystal and slightly misoriented rounded plagioclase domain.